Int. J. Adv. Res. Biol. Sci 2017
DOI: 10.22192/ijarbs.2017.04.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grape Seed Polyphenol on immune gene expression and it's Role as Antibacterial against Salmonella typhimurium infection in mice exposed to sodium nitrate

Abstract: Polyphenols especially in grape seeds have anti-inflammatory effects by immunomodulation and anti-oxidantive pathway ,as well as antimicrobial activities .The current research conducted to evaluate the immunomodulatory effect Grape Seed Polyphenol extracts (GSP) against Salmonella Typhimurium infection and fed sodium nitrate in mice.The parameters which were used in this study, including determention the bacterial clearance duration in liver tissue by counting the bacterial colony forming unit(CFU)/gram and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It was also suggested that phenolic compounds inhibit the stress-activated NF-κβ and AP-1 signaling cascade (Albaayit et al, 2020b). Phenolic compounds also enhance the immune system in the destruction of cancer cells, inhibit angiogenesis, and reduce the metastatic potential of tumors (Mohammad & Mahdi, 2017;Atiyah & Kadhum, 2021). Excavatine A, carbazole alkaloid is reported for its anticancer activity against alveolar basal epithelial cell and cervical cancer (Peng et al, 2013a).…”
Section: Expression Of Apoptotic and Anti-apoptotic Genes In Raji Cel...mentioning
confidence: 99%
“…It was also suggested that phenolic compounds inhibit the stress-activated NF-κβ and AP-1 signaling cascade (Albaayit et al, 2020b). Phenolic compounds also enhance the immune system in the destruction of cancer cells, inhibit angiogenesis, and reduce the metastatic potential of tumors (Mohammad & Mahdi, 2017;Atiyah & Kadhum, 2021). Excavatine A, carbazole alkaloid is reported for its anticancer activity against alveolar basal epithelial cell and cervical cancer (Peng et al, 2013a).…”
Section: Expression Of Apoptotic and Anti-apoptotic Genes In Raji Cel...mentioning
confidence: 99%